2008
DOI: 10.1103/physreve.78.036307
|View full text |Cite
|
Sign up to set email alerts
|

Wide-gap Couette flows of dense emulsions: Local concentration measurements, and comparison between macroscopic and local constitutive law measurements through magnetic resonance imaging

Abstract: Flows of dense emulsions show many complex features among which long range nonlocal effects pose problem for macroscopic characterization. In order to get round this problem, we study the flows of several dense emulsions, with droplet size ranging from 0.3 to 40µm, in a wide gap Couette geometry. We couple macroscopic rheometric experiments and local velocity measurements through MRI techniques. As concentration heterogeneities are expected in the wide gap Couette flows of multiphase materials, we also designe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
112
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(130 citation statements)
references
References 43 publications
(128 reference statements)
16
112
2
Order By: Relevance
“…In fact, we found that the same master line, representing eqn (5) (1) Systems in which the power-law index n z 1/2. 9,16,17,[23][24][25]54,55 In these systems n varied between 0.42 and 0.5 (centred at n z 0.47), depending on the specific surfactant and glycerol concentration in the foaming solution.…”
Section: Inside-foam Viscous Frictionmentioning
confidence: 99%
“…In fact, we found that the same master line, representing eqn (5) (1) Systems in which the power-law index n z 1/2. 9,16,17,[23][24][25]54,55 In these systems n varied between 0.42 and 0.5 (centred at n z 0.47), depending on the specific surfactant and glycerol concentration in the foaming solution.…”
Section: Inside-foam Viscous Frictionmentioning
confidence: 99%
“…58 We note that the Couette gap-width of 1mm is sufficiently small to eliminate gap-width effects. 12,13,59 The solid line in Fig. 8(a) is a comparison with our theory.…”
Section: Preliminary Experimentsmentioning
confidence: 99%
“…flow to stop abruptly at R(τ < τ 0 ), the flow profile for a yield stress fluid is smooth [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%